1974
DOI: 10.1111/j.1432-1033.1974.tb03355.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Physical Properties of a Chymotrypsin‐Like Protease of the Larva of the Hornet, Vespa orientalis

Abstract: A chymotrypsin-like endopeptidase has been purified by ion-exchange chromatography, affinity chromatography, and gel filtration. The enzyme preparation is homogeneous in the ultracentrifuge and disc electrophoresis. The enzyme is proved to be free from any other proteolytic activities. The molecular weight of the proteinase as determined with several techniques (ultracentrifugation, gel filtration and electrophoresis without dodecylsulfate) is in the range between 13 000-14000 ; however, by dodecylsulfate gel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
2
4
0
1
Order By: Relevance
“…A combination of chromatography on cation-cxchange columns and affinity chromatography yielded a pure enzymc of molecular weight 13,000-14,000-a much smaller molecule than most known chymotrypsins (29). T h e molecular weight was detcrmined by several methods-ultracentrifugation, gel filtration, polyacrylamide gel electrophoresis with and without SDS (29), and stoichiometric reactions with isotopically labeled PMSF and ZPCK (30)-all with very good agreement. Amino acid analysis showed that the enzyme contained only four cysteine residues and no methionine (30).…”
Section: H Pkoteases Of Insect Midgutmentioning
confidence: 71%
“…A combination of chromatography on cation-cxchange columns and affinity chromatography yielded a pure enzymc of molecular weight 13,000-14,000-a much smaller molecule than most known chymotrypsins (29). T h e molecular weight was detcrmined by several methods-ultracentrifugation, gel filtration, polyacrylamide gel electrophoresis with and without SDS (29), and stoichiometric reactions with isotopically labeled PMSF and ZPCK (30)-all with very good agreement. Amino acid analysis showed that the enzyme contained only four cysteine residues and no methionine (30).…”
Section: H Pkoteases Of Insect Midgutmentioning
confidence: 71%
“…The molecular masses found are those usual for chymotrypsins (Terra and Ferreira, 1994) and the pH optima determined for the different chymotrypsins conform to what is expected from the taxa they belong to (Terra and Ferreira, 1994). The same purification procedure described above has been used in several instances (Jany et al, 1974;Sakal et al, 1988;Peterson et al, 1995;Botos et al, 2000;Muharsini et al, 2001), although there are reports regarding non-lepidopteran insects in which a successful purification of chymotrypsins was attained by ion-exchange chromatography (Terra and Ferreira, 2005). It is worth-mentioning that Elpidina et al (2005) purified a chymotrypsin from T. molitor midgut that differs from the one described here in being stable during ion-exchange chromatography.…”
Section: Insect Chymotrypsin Substrate Specificitymentioning
confidence: 94%
“…The protease VCP II was purified from the larval midguts as described previously (Jany et al, 1974a), except that CM-Sephadex C-25 was replaced by CM-Sepharose C1-6B and Sephadex G-75 by Sephadex G-50. Protein Determination.…”
Section: Jany E Imentioning
confidence: 99%